2020
DOI: 10.5935/0103-507x.20200069
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the apnea test and ancillary test in determining brain death

Abstract: Objective We investigated the frequency of apnea tests, and the use of ancillary tests in the diagnosis of brain death in our hospital, as well as the reasons for not being able to perform apnea testing and the reasons for using ancillary tests. Methods In this retrospective study, the files of patients diagnosed with brain death between 2012 - 2018 were examined. The preferred test was determined if an ancillary test was performed in the diagnosis of brain death. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In 2020, 21.3% of organ donors underwent confirmatory testing in Denmark, which is in line with previous studies from other countries (24–26%) ( Sayan, 2020 ; Grzonka et al, 2023 ). These studies also reveal an increased use of ancillary tests, further emphasizing the scope and importance of appropriate protocols for ancillary tests in the determination of BD/DNC.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In 2020, 21.3% of organ donors underwent confirmatory testing in Denmark, which is in line with previous studies from other countries (24–26%) ( Sayan, 2020 ; Grzonka et al, 2023 ). These studies also reveal an increased use of ancillary tests, further emphasizing the scope and importance of appropriate protocols for ancillary tests in the determination of BD/DNC.…”
Section: Introductionsupporting
confidence: 88%
“…In a previous study, the duration of the BD/DNC protocol was associated with negative effects on donations, as increasing time intervals created the potential for confusion about the diagnosis and lead to withdrawal of consent by patient families ( Grzonka et al, 2023 ). In another study, no correlation was seen between the consent to organ donation and the time from ICU admission until the completion of the BD/DNC protocol ( Sayan, 2020 ). In our cohort, however, family consent was withdrawn in only two patients (who was excluded from the final analysis), so we attribute the declining rate of organ donation in patients investigated with ≥2 DSA to the progressive deterioration of their organs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many physicians reported performance of ancillary tests for indications not described in the AAN guidelines (such as protection from liability, more comfort with the diagnosis, and other reasons related to family request or individualized situations). Prior studies of ancillary test performance rates showed similar results; a recent retrospective review of BD patients in Turkey showed that ancillary tests were used in 83% of all patients (139/187), 74% of those who already had a positive AT, although not required per institutional policy (8). In a multicenter study from 42 Spanish ICUs analyzing 1,844 BD patients, ancillary studies were used in the vast majority of patients (95%); the authors stated that ancillary tests were only mandatory in Spain in cases where confounders exist, inability to perform the AT, or with BD due to infratentorial lesions (9).…”
Section: Discussionmentioning
confidence: 73%
“…Second, the retrospective nature of our study can weaken the results and introduce biases related to errors in data collection and missing data; however, we carefully assessed electronic medical records to limit the possibility of bias. A high frequency of ancillary test in our center may be perceived as a limitation; however, the real-world data suggest that the use of these tests are being done commonly despite national and international guidelines (7–9). Finally, attempting to predict the performance of certain investigations in a retrospective study can introduce unknown confounders that we did not adjust for (such as provider expertise, type of ICU, family and social factors, etc.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, in some official protocols, ancillary tests are used to shorten the duration of a given observation period [ 15 ], especially in unstable patients [ 23 ]. Conversely, it should be noted that in some specific constellations ancillary tests may delay the diagnosis of BD and cause damage to the organ donation target by causing confusion by false-negative or false-positive findings [ 24 ], if there is no adequate expertise in the interpretation of each of the confirmatory tests.…”
Section: Introductionmentioning
confidence: 99%